Lone terrorists: A study of run-over attacks in Israel. (January 2019) - Perry, Simon; Hasisi, Badi; Perry, Gali
There is agreement amongst scholars regarding the lack of a unique profile for lone wolf actor terrorists. Therefore, this study focuses on the characteristics of the lone attack, which has rarely been studied. The study seeks to fill these gaps, examining the element of opportunity and situational conditions by focusing on the offence/attack rather than on the offender/attacker in cases of run-over terrorist attacks. In order to shed more light on this dangerous phenomenon of lone-actor terror in general, and lone run-over attacks more specifically, this study examines all 62 run-over attacks carried out in Israel between January 2000 and March 2016. Data for this study were obtained from confidential and open sources. The study's findings reveal certain characteristics of lone run-over attacks regarding the 'four pillars of opportunity' (target, weapon, tools/training and facilitating conditions). These findings suggest that, in order to prevent run-over terrorist attacks or to minimize the damage, one should not concentrate primarily on identifying the profile of the potential attacker. Rather, effective counter-measures should identify the run-over attack elements of situational opportunities and introduce effective situational crime prevention measures that have been found to be effective in preventing non-terrorist crime.